Teacher And Students Interaction: An Exploration of Politeness Strategies - sutyrajmi s; Murni Mahmud; Sukardi Weda (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
Politeness constitutes a system of social interaction designed to facilitate interpersonal relationships by minimizing the potential for conflict and resistance across various human activities. This research aims to (1) identify the types of politeness strategies employed by teachers and students in class X1.3 at SMAN 1 Gowa,. The study adopts a descriptive qualitative approach, utilizing classroom observation and audio recordings as methods for data collection. The data were analyzed and categorized based on the politeness strategy proposed by Brown and Levinson (1987), which includes four main types: bald-on-record, positive politeness, negative politeness, and off-record strategies.The result of the study reveal one research question: (1) All four types of politeness strategies were employed by the teacher, with positive politeness emerging as the most frequently used strategy.